2014
DOI: 10.5713/ajas.2013.13307
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Protein and Energy Level in Finishing Diets for Feedlot Hair Lambs: Growth Performance, Dietary Energetics and Carcass Characteristics

Abstract: Forty-eight Pelibuey×Katahdin male intact lambs (23.87±2.84 kg) were used in an 84-d feeding trial, with six pens per treatment in a 2×2 factorial design arrangement. The aim of the study was to evaluate the interaction of two dietary energy levels (3.05 and 2.83 Mcal/kg ME) and two dietary protein levels (17.5% and 14.5%) on growth performance, dietary energetics and carcass traits. The dietary treatments used were: i) High protein-high energy (HP-HE); ii) High protein-low energy (HP-LE); iii) Low protein-hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
17
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 16 publications
13
17
0
3
Order By: Relevance
“…Also FCF-fed lambs consumed less alfalfa hay, wheat bran and barley than TMR-fed lambs. This finding is in agreement with the idea that feed intake is regulated by dietary energy density in lambs (Ebrahimi et al 2007;Ríos-Rincón et al 2014). The results on the slaughter weight disagreed with the findings of other study (Sahin et al 2003) who indicated that the slaughter weight did not differ between TMR-and FCF-fed lambs.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…Also FCF-fed lambs consumed less alfalfa hay, wheat bran and barley than TMR-fed lambs. This finding is in agreement with the idea that feed intake is regulated by dietary energy density in lambs (Ebrahimi et al 2007;Ríos-Rincón et al 2014). The results on the slaughter weight disagreed with the findings of other study (Sahin et al 2003) who indicated that the slaughter weight did not differ between TMR-and FCF-fed lambs.…”
Section: Resultssupporting
confidence: 81%
“…In the present study, relative weights of digestive tract (p<0.05) and stomach (p<0.05) and relative length of intestine (p<0.05) of TMR-fed lambs were higher than those of FCF-fed lambs (Table 3). These findings may be related to the body composition of lambs can be modified by increased energy and protein intakes (Ebrahimi et al 2007;NRC 2007;Ríos-Rincón et al 2014). Therefore, these results indicated that the FCF system did not affect the functions of the GIT traits to improving the efficiency of feed utilization in lambs although FCF system promoted the protein and energy intakes of lambs (Yıldırım et al 2013).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…After 56 days of fattening, controls lambs increased up to 11.9% in fat in the LM. Fat deposition is highly correlated to the energy density of diet, level of intake, and length of days of feeding (13,14). There were no effects of treatments on HCW, dressing percentage and size measures of components of carcasses.…”
mentioning
confidence: 99%
“…Ganancias diarias (rango de 0,230 a 0,291 kg/d), consumos de MS (rango de 0,230 a 0,291 kg/d) y eficiencias (rango de 0,180 a 0,210) similares a lo observado para el grupo control en este experimento se han informado para machos enteros cruzados de las razas Katahdin × Pelibuey consumiendo dietas de finalización libres de zeolita o de algún otro tipo de aditivo y con un contenido energético de 1,90 a 2,10 Mcal/kg de EN para mantenimiento (López-Carlos et al, 2011;Ríos et al, 2010Ríos et al, , 2014Estrada et al, 2013Estrada et al, , 2016. Por otra parte, la información sobre la respuesta productiva de borregos consumiendo dietas de finalización suplementadas con zeolitas es escasa.…”
Section: Resultados Y Discusiónunclassified